Excimer‐Based On‐Off Bis(pyreneamide) Macrocyclic Chemosensors. Issue 1 (25th December 2017) - Vishe, Mahesh; Lathion, Timothée; Pascal, Simon; Yushchenko, Oleksandr; Homberg, Alexandre; Brun, Elodie; Vauthey, Eric; Piguet, Claude; Lacour, Jérôme
Abstract : A series of bis(pyreneamide) macrocycles, synthesized in two steps from THF, THP, oxepane and 1, 4‐dioxane, are tested as chemosensors for a large range of mono‐, di‐ and trivalent cations. In their native states, these macrocycles exhibit a strong excimer fluorescence that is quenched upon the addition of the metal ions (alkaline, alkaline earth, p ‐, d‐, and f ‐block metals). UV‐Vis spectrophotometric titrations, cyclic voltammetry, excimer fluorescence quenching, and transient absorption spectroscopy experiments helped characterize the On‐Off changes occurring upon binding and demonstrate that the highest stability constants are obtained with divalent cations Ca 2+ and Ba 2+ specifically. Abstract :